COVID-19: Heterogeneous Excess Mortality and “Burden of Disease” in Germany and Italy and Their States and Regions, January–June 2020 - Morfeld, Peter; Timmermann, Barbara; Groß, J. Valérie; Lewis, Philip; Cocco, Pierluigi; Erren, Thomas C. (Frontiers in Public Health, 2021)
Total mortality and “burden of disease” in Germany and Italy and their states and regions were explored during the first COVID-19 wave by using publicly available data for 16 German states and 20 Italian regions from January 2016 to June 2020. Based on expectations from 2016-2019, simplified Standardized Mortality Ratios (SMRs) for deaths occurring in the first half of 2020 and the effect of changed excess mortality in terms of “burden of disease” were assessed. Moreover, whether two German states and 19 Italian cities appropriately represent the countries within the European monitoring of excess mortality for public health action (EuroMOMO) network was explored. Significantly elevated SMRs were observed (Germany: week 14-18, Italy: week 11-18) with SMR peaks in week 15 in Germany (1.15, 95%-CI: 1.09-1.21) and in week 13 in Italy (1.79, 95%-CI: 1.75-1.83). Overall, SMRs were 1.00 (95%-CI: 0.97-1.04) in Germany and 1.06 (95%-CI: 1.03-1.10) in Italy. Significant SMR heterogeneity was found within both countries. Age and sex were strong modifiers. Loss of life expectancy was 0.34 days (1.66 days in men) for Germany and 5.3 days (6.3 days in men) for Italy [with upper limits of 3 and 6 weeks among elderly populations (≥ 65 years) after maximum potential bias adjustments]. Restricted data used within EuroMOMO neither represents mortality in the countries as a whole nor in their states and regions adequately. Mortality analyses with high spatial and temporal resolution are needed to monitor the COVID-19 pandemic's course.